PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH PADAMATA PELAJARAN DASAR-DASAR TEKNIK MESIN DI SMK - Wahid Maulana, - (2023)
Low learning outcomes were discovered in Mechanical Engineering students from the UAS results for odd semester 2022/2023 in the Basics of Mechanical Engineering or Basic Skills Program 2 (DPK 2) disciplines. Overall, the learning results have not climbed much above the KKM, which is 76. One of the causes is because students lack interaction because learning does not engage students. The Problem-Based Learning Model is implemented as an alternative variety of learning, which is applied at SMKN 6 Bandung class X TP 1 as a sample application that coincides with the Education Unit Field Introduction Program (PPLSP). Based on the problems above, this research intends to find out in which category boosts learning results, in the implementation of the PBL model and how are students' responses to the PBL model? The research is categorized in the Quantitative category of pre-experimental approaches employing a one group pretest-posttest research design. The sample is class X TP 1 totaling 35 persons taken with the Cluster Sampling technique. Answering the above problems, a study was carried out with a pre-test before therapy and a post-test after treatment. Calculation of the increase in value and comparison of the data before and after treatment with the N-Gain formula were carried out. After the treatment was carried out on the sample using the study instrument test questions and questionnaires, obtaining predicated N-Gain results "Currently". In line with student responses, the findings reveal "good" and the model is declared good. After study on the application of this model it was decided that the PBL model was at least able to increase student learning outcomes with the results of the N-Gain category being strengthened also by the results of students' opinions on this model with good opinions for use